Interallelic and intergenic conversion events could induce differential evolution of the two rabbit immunoglobulin kappa light chain genes. - Mariame, B (1987)
Contrary to the situation in humans or mice, where the constant region (C) of the Immunoglobulin (Ig) kappa (kappa) light chain is encoded by a single gene, the rabbit possesses two C kappa genes: C kappa 1 and C kappa 2. However, in domestic rabbits, the vast majority of the immunoglobulins have a light chain of the kappa 1 isotype, which is expressed under four complex, highly divergent allelic forms: b4, b5, b6 and b9. In previous papers, we have shown that this high level of divergence was due, at least partly, to conversion events of the kappa 1 by the kappa 2 locus. Up to now, little was known about the evolution of the C kappa 2 gene. Here, we report sequences of the C kappa 2 genes in three different haplotypes, and show that, in contrast to the situation in the kappa 1 locus, the three analysed C kappa 2 alleles are identical (or only differing by one silent substitution). This suggests that intergenic conversion, which introduced most of the divergence in the kappa 1 locus, is not reciprocal and is unidirectional from kappa 2 towards kappa 1. To explain the small number of silent substitutions in the C kappa 2 gene and its remarkable conservation, we propose an extended model of multigenic family evolution, which postulates that gene conversion events occur between linked genes as well as between alleles.